(untitled) (The Journal of Plant Protection Sciences, 2020)
As conceived in the “West”, Precision Agriculture (PA) may be suitable for capital-intensive, high turnover economy, high technology monoculture and controlled management of a single major soil borne pathogen or pest across vast cultivated area but not for the peasant farming or the pest complex ridden unaided agriculture as in India. PA is not about an abstract of characterization. The specific values indicating variations in population at exact grids and helping the individual farmer in decision making in pest management at varied pesticide doses depending on varied soil pest population intensity and spatial distribution. Often it ends up in reducing the quantum of a pesticide threatened with withdrawal. We understand Appropriate PA (Appropriate Precision Agriculture, APA) as Site-Specific Appropriate Precision Agriculture (SSAPA) applied to cropping system management with withdrawal.